Does wearing swimming goggles affect corneal morphology in keratoconic eyes? - Ulusoy,Döndü Melek (2020)
ABSTRACT Purpose: A significant transient increase in intraocular pressure in individuals wearing swimming goggles has been demonstrated in previous studies. These findings suggested that wearing swimming goggles could represent a significant risk factor for worsening of corneal parameters in patients with keratoconus who swim regularly. The aim of this study was to investigate corneal parameters in patients with keratoconus after wearing swimming goggles. Methods: Comprehensive ocular examinations were performed on 74 eyes of 37 patients with keratoconus. Measurements of the corneal front keratometry values (Kflat, Ksteep, and Kmax), central corneal thickness, corneal apex thickness, thinnest corneal thickness, corneal volume, anterior chamber volume, anterior chamber depth, and iridocorneal angle were performed in outpatient clinics using a Pentacam® Scheimpflug camera (Oculus, Wetzlar, Germany) before the patients wore swimming goggles and after they wore swimming goggles for 1, 10, and 20 min. A p-value of <0.05 was regarded as statistically significant. Results: The average values before and after wearing swimming goggles for 1, 10, and 20 min were 52.72 ± 5.36, 52.64 ± 5.52, 52.62 ± 5.38, and 52.22 ± 4.86, respectively (p=0.257). The average values before and after wearing swimming goggles for 1, 10, and 20 min were 46.01 ± 3.17, 46.09 ± 3.17, 46.06 ± 3.26, and 46.04 ± 3.17, respectively (p=0.426). The average values before and after wearing swimming goggles for 1, 10, and 20 min were 49.02 ± 3.56, 49.06 ± 3.61, 49.08 ± 3.62, and 49.07 ± 3.61, respectively (p=0.750). No other corneal parameters showed changes after wearing swimming goggles (p>0.05). However, the anterior chamber volume markedly decreased after wearing swimming goggles (p<0.001). Conclusions: These findings suggested that the short-term use of swimming goggles does not increase the risk of corneal parameter worsening in patients with keratoconus.